2017
DOI: 10.1161/circresaha.116.309528
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-33 Controls Adaptive Fibrotic Response in the Remodeling Heart by Preserving Lipid Raft Cholesterol

Abstract: Rationale: Heart failure and atherosclerosis share the underlying mechanisms of chronic inflammation followed by fibrosis. A highly conserved microRNA (miR), miR-33, is considered as a potential therapeutic target for atherosclerosis because it regulates lipid metabolism and inflammation. However, the role of miR-33 in heart failure remains to be elucidated. Objective: To clarify the role of miR-33 involved in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 68 publications
2
34
0
Order By: Relevance
“…A profibrotic role for miR-33 has been also reported in cardiac fibrosis, as cardiac fibroblast-specific deficiency of miR-33 reduced cardiac fibrosis in response to pressure overload by transverse aortic constriction. The proposed mechanism underlying this response was that deficiency of miR-33 impaired cardiac fibroblast proliferation because of altered lipid raft cholesterol content (58,59). In the kidney, we demonstrate an important role for miR-33 in the regulation of FAO in TECs, which may be relevant to explain its effects on fibrogenesis.…”
Section: Discussionmentioning
confidence: 70%
“…A profibrotic role for miR-33 has been also reported in cardiac fibrosis, as cardiac fibroblast-specific deficiency of miR-33 reduced cardiac fibrosis in response to pressure overload by transverse aortic constriction. The proposed mechanism underlying this response was that deficiency of miR-33 impaired cardiac fibroblast proliferation because of altered lipid raft cholesterol content (58,59). In the kidney, we demonstrate an important role for miR-33 in the regulation of FAO in TECs, which may be relevant to explain its effects on fibrogenesis.…”
Section: Discussionmentioning
confidence: 70%
“…In addition the role of miR-33 in regulating lipid accumulation in macrophages and hepatocytes, Nishiga et al reported that miR-33 preserves lipid raft cholesterol content in cardiac fibroblasts through the regulation of ABCA1 expression and maintains adaptive fibrotic response in the remodeling heart [50]. Surprisingly, miR-33 deficient mice showed impaired systolic function after thoracic aortic constriction (TAC).…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that lipid rafts play a role in RA-induced exit from pluripotency. To verify this indication, we also disrupted rafts via treating the early differentiating cells with cholesterol depletion reagent MBCD [47-50]. Compared to the group treated with RA only (green), cells co-treated with MBCD and RA exhibited delayed pluripotency exit, as revealed by the slower decrease of Oct4 and GFP expression (red, Figure 3f ), supporting that rafts facilitate the early differentiating cells to exit from pluripotency.…”
Section: Resultsmentioning
confidence: 86%